Shifting views and building bonds: Narratives of internationally adopted children about their dual culture. (June 2018) - Benoit, Laelia; Harf, Aurélie; Sarmiento, Laura; Skandrani, Sara; Moro, Marie Rose
American literature on international adoption suggests that adoptees' pride in the culture of their birth country improves their self-esteem and helps them to cope with experiences of racism. Parents are therefore encouraged to teach their adopted children multicultural skills to improve their psychological well-being. French psychologists, on the contrary, suggest that adoptees should feel fully members of their adoptive country and families. These practices shed light on the respective multicultural and universalist paradigms in the US and France. Few papers, however, consider the opinions of adoptees. This study explores internationally adopted children raised in France and their spontaneous curiosity about their birth country. The present study used semi-structured interviews with 19 adoptees aged 8–18 years old, to explore their attitudes towards the culture of their birth country. Transcripts of recorded interviews were analyzed according to interpretative phenomenological analysis. While there was striking consistency of interest in birth countries, adoptees' expression of curiosity varied across time. Children described distinctive goals: knowing more about their history, finding relatives, becoming a multicultural citizen, or simply helping people. Their parents' involvement was thus seen as helpful, but adoptees stress the need to feel ready and may prefer independent ways of learning about their birth country. Adoptees' multiple feelings of belonging derive not only from multicultural training but from a lifelong construction of self. Professionals and parents may need to adapt to adoptees' individual development, distinctive time frames, and ways of learning to provide better support to them.